2009
DOI: 10.1007/s00468-009-0336-x
|View full text |Cite
|
Sign up to set email alerts
|

No evidence of spatial root system segregation and elevated fine root biomass in multi-species temperate broad-leaved forests

Abstract: Differences in spatial rooting patterns among coexisting species have been recognized as an important mechanism for generating biodiversity effects on ecosystem functioning. However, it is not yet clear whether complementarity in root space exploration is a universal characteristic of multi-species woody communities. In a temperate broad-leaved forest with a mosaic of speciespoor and species-rich stands, we tested two hypotheses related to putative below-ground 'overyielding' in more diverse forests, (1) that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(47 citation statements)
references
References 49 publications
3
42
0
Order By: Relevance
“…Fine root biomass of a single tree within the distance of 2 to 5 m (cluster radius) from the stem was approximately 400 to 600 gm −2 (0-40 cm depths) and did not differ between species. Meinen et al (2009b) found a high degree of root system overlap in mixed stands. The change of fine root biomass with increasing stem distance suggest that fine roots in our soil samples originated mainly from the three cluster trees.…”
Section: Tree Species Effect On Soil Acidity and Exchangeable Cationsmentioning
confidence: 92%
See 1 more Smart Citation
“…Fine root biomass of a single tree within the distance of 2 to 5 m (cluster radius) from the stem was approximately 400 to 600 gm −2 (0-40 cm depths) and did not differ between species. Meinen et al (2009b) found a high degree of root system overlap in mixed stands. The change of fine root biomass with increasing stem distance suggest that fine roots in our soil samples originated mainly from the three cluster trees.…”
Section: Tree Species Effect On Soil Acidity and Exchangeable Cationsmentioning
confidence: 92%
“…Meinen et al (2009aMeinen et al ( , 2009b determined total root biomass and root distribution of different tree species close to our cluster sites. They found no evidence of spatial root system segregation or elevated root biomass in multi-species sites.…”
Section: Tree Species Effect On Soil Acidity and Exchangeable Cationsmentioning
confidence: 99%
“…Limestone already occurred at shallow soil depths (0.6-1.0 m) limiting the rooted soil volumes. Stand fine root biomass in the area decreased exponentially with soil depth with 63-77 % being concentrated in the upper 20 cm (Meinen et al, 2009).…”
Section: Study Areamentioning
confidence: 97%
“…However, few studies have examined belowground productivity in mixtures and even fewer have compared above-and belowground productivity (Forrester et al, 2006;Epron et al, 2013). Belowground overyielding has not been demonstrated to occur in mature temperate forests (Meinen et al, 2009a(Meinen et al, , 2009bJacob et al, 2013) although root differentiation led to higher fine root productivity in young stands (Lei et al 2012) whereas in boreal forests fine root overyielding was observed in mature stands originated after fire (Brassard et al, 2011). Interspecific competition can also have a strong impact on crown structure (Bayer et al, 2013) and crown allometry .…”
Section: Species Interaction and Species Richness -Ecosystem Functioningmentioning
confidence: 99%